Hand Surgeons Are Tackling Tougher Scaphoids: A Study of ABOS Candidate Data. (March 2023) - Nicholson, Tyler; Dunn, John C.; Nesti, Leon J.
Background: This study will evaluate whether those who have completed a hand fellowship treat a disproportionate number of scaphoid fractures based on recent American Board of Orthopaedic Surgery (ABOS) data. We hypothesize that surgeons who have completed a fellowship in hand surgery will address most surgically treated scaphoid fractures, particularly those with fracture nonunions or requiring graft. Methods: We queried the ABOS database for case log information submitted for part II of the ABOS examination. This search included all cases with Current Procedural Terminology codes for procedures related to scaphoid fixation. Demographic information, case volume, type of case, and complication rate were compared for hand fellowship–trained surgeons and those who had completed other fellowships as well as non-fellowship-trained surgeons. Results: During the study period, 1686 surgeons reported treating 4244 scaphoid fractures. Of these surgeons, 1180 had completed a hand surgery fellowship. Hand fellowship–trained surgeons were shown to have operatively treated more scaphoid fractures both in total volume and on a per-surgeon basis. Hand fellowship–trained surgeons were also found to have performed a significantly higher proportion of difficult cases, which were those listed as being a malunion/nonunion or those incorporating a pedicle graft. There was no difference in the complication rate between the 2 groups. Conclusion: Among those orthopedic surgeons reporting case information for part II of the ABOS certification examination, statistically significant differences exist in case volume and case difficulty among surgeons with different areas of fellowship training. Complication rates increase with patient age and examination year.